Intensive reading and extensive reading in teaching reading comprehension - Naely Muchtar (Universitas Negeri Yogyakarta, 2020)
The research investigated the implementation of Intensive Reading (IR) and Extensive Reading (ER) that is suitable for English class in Polytechnic that focuses on the ability of English practice. This research is a Classroom Action Research (CAR), which consists of three stages, namely pretest, treatment, and posttest. Based on the results of the pretest, it can be concluded that reading skill of the second semester students from Computer and Networking Engineering study program before the implementation of IR and ER method were still relatively low, in the classification of poor (25%) represented by 11 students and in very poor classification (18.2%) achieved by 8 students. After three times treatment by using three different articles for English reading text, the reading skill of students increased significantly in the presence of 2 students (4.5%) in the classification of very good and there were only 6 students were in poor and very poor classification. Based on posttest result, reading skill of students enhance significantly with 5 students (11.4%) were in very good classification.